Exploring the Role of Fear of Missing out (FOMO) on consumer behaviour: A study of Spending, Trash Talking and Anxiety - Muhammad Fahmi (Journal of Management Practices, Humanities and Social Sciences, 2024)
Since excessive spending, trash talk, and consumer worry frequently result in undesirable effects including depression, social anxiety, and debt, it is imperative to understand their causes. The purpose of this research is to examine how excessive spending, trash talk, and customer anxiety are impacted by FOMO, harmonious brand passion, and obsessive brand passion. We gather information from 421 customers and analyse it using partial least squares. The study backs up the attachment theory and social comparison theory, which distinguish between obsessive and harmonious types of brand enthusiasm, with the latter being a bad thing. The results unequivocally support the connection between both forms of brand love and FOMO. Consumer anxiety, trash talk, and excessive spending are all more significantly predicted by obsessive passion. Additionally, the study reveals that the relationship between consumer anxiety, trash talking, and excessive spending and FOMO is mediated by harmonizing brand passion. We suggest marketing tactics that support consumers' FOMO-driven passions, promote and cultivate harmonious passion, cultivate compulsive passion in a more responsible way, and concentrate on brand-passion-driven marketing to consumers.